Piper aduncum Essential Oil Rich in Dillapiole: Development of Hydrogel-Thickened Nanoemulsion and Nanostructured Lipid Carrier Intended for Skin Delivery - Simone Braga Carneiro; Tainá Kreutz; Renata Pereira Limberger; Helder Ferreira Teixeira; Valdir Florêncio da Veiga Júnior; Letícia Scherer Koester (MDPI AG, 2022)
The essential oil extracted from the leaves of Piper aduncum, an aromatic plant from the Amazon region, is rich in dillapiole and presents anti-inflammatory activity. In this study, nanoemulsions (NE) and nanostructured lipid carriers (NLC), which are biocompatible nanostructured systems of a lipid nature, were prepared by high-pressure homogenization for the yet unexplored skin delivery of dillapiole. The addition of hydroxyethylcellulose produced hydrogel-thickened NE or NLC in view to improving the viscosity and skin adherence of the nanoformulations. Formulations were characterized with respect to dillapiole content, droplet size, polydispersity index, zeta potential, morphology, rheological behavior, bioadhesion, skin permeation profile, and in vitro irritancy (HET-CAM). The formulations developed presented spherical, homogeneous nanometric particle size (around 130 nm), narrow polydispersity index (<0.3), and negative zeta potential (around −40 mV). Dillapiole content was slightly lower in NLC compared to NE since the production process involves heating. The hydrogels containing nanocarriers showed pseudoplastic behavior with bioadhesive characteristics. The developed formulations exhibited a controlled release profile, dillapiole delivery up to the dermis, the layer of interest for anti-inflammatory potential, and low irritant potential in the chorioallantoic membrane (HET-CAM). Both hydrogels-thickened NE and NLC seemed to be promising formulations for skin delivery of Piper aduncum essential oil.